PEMANFAATAN SISTEM INFORMASI MANAJEMEN UNTUK MENINGKATKAN KUALITAS LAYANAN PENDIDIKAN DI MTS PPI 50 LEMBANG - Marlina, Lenny; Safwandy Nugraha, Mulyawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study discusses how to utilize the Management Information System (SIM) in improving the quality of educational services at MTs PPI 50 Ciputri Lembang. With the increasing demands of society for the quality of education, educational institutions need to adapt to information technology. Management Information System (MIS) is considered as an effective solution to improve efficiency and effectiveness in managing academic, administrative, and student service data. The purpose of this study is to analyze the extent of the benefits of MIS in improving the quality of education services at MTs PPI 50 Ciputri Lembang, in addition to identifying factors that influence the implementation of MIS and its impact on learner and parent satisfaction. This research uses a qualitative approach with data collection techniques through interviews, observations, and documentation studies. The results showed that the implementation of SIM in the form of utilizing an application system consisting of EMIS (Education Management Information System) and Serasi Mobile at MTs PPI 50 Ciputri Lembang has had a positive impact, such as increasing data accuracy, accelerating administrative processes, and increasing student and parent satisfaction with the educational services provided. In addition, challenges in the implementation of SIM, such as training needs and technological infrastructure were also identified to be continuously improved. This research highlights